2021
DOI: 10.3390/fi13010020
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of Social Networking Sites and Apps on the Social Capital of Saudi Postgraduate Students: A Case Study

Abstract: With the increased use of Social Networking Sites and Apps (SNSAs) in Saudi Arabia, it is important to consider the impact of this on the social lives of tertiary students, who are heavy users of such technology. A mixed methods study exploring the effect of SNSAs use on the social capital of Saudi postgraduate students was conducted using a multidimensional construct of social capital, which included the components of life satisfaction, social trust, civic participation, and political engagement. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(105 reference statements)
1
2
0
Order By: Relevance
“…A similar linear relationship between social capital and life satisfaction was demonstrated in a study conducted in the USA by Calcagnini and Perugini (2019). In the study conducted by Alghamdi and Plunkett (2021), it was found that students' social capital has a strong positive effect, especially on life satisfaction. Geraee, Eslami, and Soltani (2019) remarked that social capital's most vital precursor is life satisfaction.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar linear relationship between social capital and life satisfaction was demonstrated in a study conducted in the USA by Calcagnini and Perugini (2019). In the study conducted by Alghamdi and Plunkett (2021), it was found that students' social capital has a strong positive effect, especially on life satisfaction. Geraee, Eslami, and Soltani (2019) remarked that social capital's most vital precursor is life satisfaction.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
“…When examining the studies conducted upon evaluating the relationship between social capital and life satisfaction from the point of young people, James Coleman (1988) stated that social capital leads to satisfaction by affecting young people's educational attainment. The study conducted by Alghamdi and Plunkett (2021) suggests that students' social capital has a substantial impact on life satisfaction particulary. In the study conducted by Geraee, Eslami and Soltani (2019) aiming to investigate the relationships between social capital, social media use and life satisfaction and to determine the effect of social media use on the relationship between social capital and life satisfaction in young people, it was found that social capital is the most vital precursor of life satisfaction.…”
Section: Figure 1 Social Capital Dimensions and Its Definitionsmentioning
confidence: 99%
“…The Impact of Social Interaction. Satisfying the need to belong to a group and engage in SIs represents the main motivation that drives individuals to use social media (Alghamdi & Plunkett, 2021;Baek et al, 2011;Hennig-Thurau et al, 2004;Muntinga et al, 2011;N. Park et al, 2009;Whiting & Williams, 2013).…”
Section: Literature Review Theoretical Framework and Hypotheses Devel...mentioning
confidence: 99%